New Audiovisual Trends with the One-person Consumme as the New Reality: From group experience to personalized individual consumption - Rozados Lorenzo, Andrés José (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The emergence of different broadcasting and streaming companies have involved the proliferation of new films and series available everytime and everywhere. This supposes a new conception oriented to a new dynamics that converts the audiovisual experiences with a group of people- going to the cinema, watching TV at home- to a one-person experience.- through an electronic device-. The aim is to analyze if this situation is merely circumstantial, or, a new trend that means that we have a new model with customized and one-person audiovisual products.